Time to question the NHS diabetes prevention programme. (7th September 2015) - Barry, Eleanor; Roberts, Samantha; Finer, Sarah; Vijayaraghavan, Shanti; Greenhalgh, Trisha
Abstract : Public Health England's focus on individual behaviour change is unlikely to stem the epidemic of type 2 diabetes